The effect of within-day energy distribution on lean body mass and body fat in athletes: A systematic review - Murlasits, Z.; Cantrell, G. S.; Kneffel, Z. (International Journal of Sports Science & Coaching, 2025)
Nutritional practices have a significant effect on exercise performance as they determine not only acute energy availability for sport activities, but also long-term changes in body composition. This review summarizes the available evidence and explores the critical relationship between within-day energy balance and body composition, emphasizing the importance of even energy distribution for optimal athletic performance and health. Findings revealed that within-day energy balance is a significant factor in the regulation of body composition in athletes, and that negative within-day energy balance may impair muscle protein synthesis and promote fat accumulation. The available evidence suggests that athletes should have an energy intake that dynamically matches requirement (i.e., the portion of the day when energy expenditure is higher, should be matched with a higher energy intake) to avoid prolonged periods of energy restriction. The reviewed investigation emphasized the importance of hourly energy balance assessment, because reliance on 24-h energy status may be insufficient in athletes. However, due to the dearth of scientific evidence in competitive athletes, more research is needed to determine the optimal within-day energy balance, considering training goals, individual differences, and dietary preferences.